Thinking through Decolonial Pedagogies - Parent, Marcel (Arc, 2023)
Developed through the Decolonization and the Study of Religion Workshop Series, this paper will explore some concerns about decolonizing pedagogy in theory, practice, and the classroom. Weaving insights from a set of important thinkers in the field – like Achille Mbembe, Linda Tuhiwai Smith, Eve Tuck and Ruben A. Gaztambide-Fernandez, Walter Mignolo and Catherine Walsh, Anabal Quijano, and Paulette Regan – the aim of the paper is to introduce some questions for pedagogues to think about in relation to the question of decolonizing pedagogies and to some of the discussions had at the workshop. The paper explores topics and discussions about structural critiques of the university, material versus epistemic analyses of decolonization, learning and unlearning as a central method in decolonization, the importance of how to make space for African and Indigenous Traditional Knowledges, and thinking about how to unpack power relations in the classroom and curriculum. The paper is more concerned with opening dialogue and making space for insights than an attempt to answer definitively questions of decolonization and pedagogy.